Development of a Finite Element Model for Thermal Analysis of Friction Stir Welding (FSW) - Meyghani, B. (Institute of Physics Publishing, 2019)
Almost 2 decades ago, TWI had successfully introduced the Friction Stir Welding (FSW). During FSW, temperature increases because the friction and plastic deformation which begin at the same time. There are various reports on the assumptions and hypotheses in modelling the heat generation and the deformation of the material, however a consensus about modelling of the process is still to be reached. Over the years, scholars had proposed many numerical approaches, particularly Lagrangian, Eulerian and Arbitrary-Lagrangian-Eulerian (ALE). Researchers have deemed that choosing the most suitable numerical approach is one of the most challenging phases for FSW thermal modelling. This is because using the wrong numerical model could lead to issues such as divergence problems and high mesh distributions. Such problems could escalate when the welding transverse or rotational speeds increase. Thus, in this paper, global (structural component) level analysis was conducted, defining the problem in the Lagrangian setting. Meanwhile, an apropos kinematic framework was used at the local level. This framework uses the efficient combination Eulerian and Lagrangian descriptions for various welding speeds through the use of ABAQUSÂ® software. The results from the temperature evaluation of the welding process are detailed in the paper. The result of the comparison between the experimental and simulated model indicates that the numerical model demonstrates the prospective methodology and its ability to accurately examine the FSW processes during different welding speeds. Â© Published under licence by IOP Publishing Ltd.